THE POWER OF INFLUENCE: EXAMINING KEY FACTORS DRIVING INDONESIAN HIGH SCHOOL STUDENTS' ENROLLMENT INTENTIONS IN PRIVATE UNIVERSITIES - Juniarty; Rendy Pahlevi (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study aims to investigate how social media marketing, electronic service quality, word of mouth, emotional value, and energizing value affect the enrollment intentions of high school students in Indonesia who are considering higher education. The findings of this study offer important insights into the ways in which factors like social media marketing, electronic service quality, word of mouth, along with emotional and energizing value, can affect students' intentions to pursue further education at the university level. This study offers significant insights for higher education institutions seeking to enhance marketing methods to attract potential students using social media and elevate the quality of electronic services. Higher education institutions must prioritize the stability and durability of their digital platforms, cultivate good connection with the student body, and consistently update tactics and features to meet the expectations of potential students. This approach is promising for attracting prospective students and increasing their engagement and dedication to the university. The findings demonstrate that social media marketing and the quality of online services positively influence emotional value and motivation, subsequently enhancing the intention to enroll. Additionally, recommendations from family, friends, and alumni play a significant role in influencing students' decisions to enroll. The results indicate that higher education institutions ought to enhance their social media approaches, bolster their digital services, and foster impactful emotional and motivational experiences.